Theoretical, Pedagogical, and Practical Views of Genre Based Instruction - Morganna, Ruly (ENGLISH FRANCA : Academic Journal of English Language and Education, 2017)
This paper is written under the purpose of exploring in details about one of popular language teaching methods namely Genre based Instruction (GBI). GBI as how it is today is very famous to be applied for teaching writing where the same case occurs in Indonesia in that GBI is implemented into the English classroom for teaching English writing. GBI is uniquely powerful in its substance since it not only focuses on the process of writing itself, but also stresses on the quality of writing work. This teaching method makes students learn a language as how it is used in a particular social setting because that is the obvious phenomenon that happens when people use a language. Therefore, this teaching method underlies its essence on teaching language meaningfully based on the social staging. In this paper, there are several elements which are discussed regarding GBI. They encompass its theories including linguistic principles and learning principles, both pedagogical and practical views in the classroom, and a brief practical view about GBI in Indonesia.